Three Rooms - Polly Stanton (2018)
BACKGROUND Three Rooms is a work that is positioned within the field of acoustic ecology that depicts edge lands – isolated rural settings. This community of practice presents a survey of places situated outside mainstream society. Rarely do these works incorporate visuals aesthetics or aspire to artistic innovation through the specific use of technology. One exception is the sound work ‘Absent Presence’ (Philip Samartzis, 2016), which uses an array of specialist omni directional microphones and still images to capture Katabatic wind in Antarctica. Inspired by Samartzis’s work, Three Rooms utilizes specialist sound recording technology and includes the visual medium of video to render a multidimensional audio-visual experience of Iceland’s rarely heard or seen edge lands. CONTRIBUTION Three Rooms is a 10-minute video and multichannel sound installation that explores the interior remnants of an abandoned farmhouse in Iceland's remote Westfjords region. The work expands the field of acoustic ecology by utilizing ambisonic microphones and video footage filmed at the recording sites to present a detailed and expansive audio-visual rendering of Iceland’s most remote sub-arctic community. SIGNIFICANCE The project is significant through its use of specialist sound recording technology (ST450 SoundField ambisonic mic) to explore the abandoned community of Hornstrandir. This work was created during a residency at the NES artist-in-residence program in Iceland. The residency program and production of the work was supported by a development grant from an Australia Council for the Arts ($10,000). The resulting work was included in the sound art exhibition Super Field, which was curated by The Bogong Centre for Sound Culture at RMIT Design Hub in 2018. The exhibition environment was designed by architects and 2018 Venice Architecture Biennale creative directors Baracco+Wright. The three-month exhibition included a 40-page catalogue and the research symposium ‘Open Field’, which profiled the work's associated fieldwork and ...